#TITLE_ALTERNATIVE# - FIRDAUS (nim: 15113006), ANDI
The role of Ground Control Point (GCP) in photogrammetry, particularly in aerial triangulation process, are one of the essential factor to obtain good quality result. However, behind its vital role there is a complex process to survey a GCP that sometimes become an obstacle such as time and cost needed in data acquisition or photogrammetry processing. This research aims to evaluate an alternative solution from the utilization of GCP with an application of aerial control point (ACP) as a result of GNSS positioning for Unmanned Aerial Vehicle (UAV)-Photogrammetry purposes. With ACP, it is possible to put control point in exposure point for every aerial photos taken in data acquisition. The GNSS observation method used to obtain this ACP is Post-Processing Kinematic (PPK) GNSS Positioning so the position of exposure point can be determined during flight mission. The result of photogrammetry process using ACP are being compared with the one controlled with GCP through RMSE value check on Independent Check Point (ICP) in a purpose to obtain conclusion of this research. Best findings in this research shows the value of RMSE check for ACP are smaller than the one with GCP, where the difference value are 0.035 m in horizontal axis and 0.118 m in vertical axis. The RMSE value check are done in a various data processing scenario and case study that will be explained in this undergraduate thesis.